Relevancia de la infraestructura y análisis de los sobrecostos que genera su déficit - Urrunaga, Roberto (2009)
The quantity and quality of infrastructure cause positive effects over economic growth, income distribution, and other variables that measures people welfare. On the other hand, the lack of infrastructure lets the costs rise (transaction costs) and the user’s demand goes down (deadweight loss). This paper shows briefly the benefits of public services infrastructure over a sample of Latin American countries, and then focuses on the excess of costs (overcharges) that arise because of the lack of infrastructure. Regarding the last topic, this paper presents a methodology for the estimation of transaction costs and deadweight loss in the cases of inadequate road’s and port’s infrastructure, and then applies this methodology to the IIRSA Norte turnpike and the port of Yurimaguas. The results about the infrastructure benefits confirm the findings of previous papers, and the results of overcharges are underestimates because of lack of information to calculate all the transaction cost items.